Differences in Experiences of Discrimination in Accessing Social Services Among Transgender/Gender Nonconforming Individuals by (Dis)Ability. Issue 2 (3rd April 2017) - Kattari, Shanna K.; Walls, N. Eugene; Speer, Stephanie Rachel
ABSTRACT: Transgender and gender nonconforming (GNC) individuals frequently experience discrimination and potentially a lack of respect from service providers, suggesting they have decreased access to professionals with cultural competency. Similarly, people with disabilities experience higher levels of discrimination in social services than their nondisabled counterparts. From an intersectional perspective, this study examines rates of discrimination in accessing social services faced by transgender and GNC people, comparing across ability. Data indicate that although transgender and GNC individuals of all abilities experience gender-based discrimination when accessing social services, those with disabilities experience higher levels of antitransgender discrimination in mental health centers, rape crisis centers, and domestic violence shelters.